Finding solution of differential equation using euler numerical method dy/dx=0.3y−10 and 0<=x<=3 and x=0,y=40.

asigurato7 2022-07-18 Answered
Finding solution of differential equation using euler numerical method d y d x = 0.3 y 10 and 0 x 3 and x = 0 , y = 40.
What i have tried
y n = y n 1 + h f ( x n 1 , y n 1 )
Where f ( x , y ) = 0.3 y 10.
I have a doubt that what should i take width interval h in above question.(which is not mention here)

Can anyone please explain me what i take value of h. Thanks
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Ragazzonibw
Answered 2022-07-19 Author has 15 answers
You just wrote the euler algorithm. Notice that f ( x n , y n ) = 0.3 y n 10. Thus,
y n = y n 1 + h ( 0.3 y n 1 10 ) = ( 1 + 0.3 h ) y n 1 10 h
Now, since you are not given h, you may pick for instance h = 1, for simplicity. Then, you have an algorithm:
{ y n = 1.3 y n 1 10 x 0 = 0 y 0 = 40
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2022-08-22
I am asked to solve the following problem. Use Euler's modified method to solve the initial value problem d x d t = 1 + x 2 t , 1 t 4 , x ( 1 ) = 0
The step size is not given here. Now, I can solve this using Euler's method but I am not able to find the formula for modified one in the mentioned textbook. So, I need the method here. I need to use the following as textbook: Brain Bradie, A friendly Introduction to Numerical Analysis (Pearson)
asked 2022-10-02
The original functional was   J [ x ] = 0 1 x f ( x ) f ( x ) d x with   h ( x ) = x. Solved for the Gateau derivative:   J [ f , h ] = 0 1 x f ( x ) h ( x ) d x + 0 1 x f ( x ) h ( x ) d x. To use the Euler method,   L = x f x + x f x such that   L f = x 2 , L f = x 2 , d d x L f = 2 x. However, I must have made a mistake that I can't see with that because it yields   x 2 2 x = 0 which doesn't tell me anything about what   f must be.
asked 2022-08-06
A ball is dropped from the top of a tall building. If air resistance is taken into account, recall that the downward velocity v of the ball is modeled by the differential equation:
d v / d t = g p v
where g = 9.8 m / s e c 2 is the acceleration due to gravity, and p = 0.1 is the drag coefficient. Assuming the initial velocity of the ball is zero, use Euler’s method with a step size of h = .25 sec to estimate the velocity of the ball after one second. Keep track of three decimal places during the calculation.

I just started learning the Euler's method. Can someone help me with this problem. I know that:
d v / d t = f ( v , t ) = g p v
I plug the numbers given into the equation: d v / d t = 9.8 .25 v
change of x = step size (h) = .25
I think ( v ( 0 ) , t ( 0 ) ) = ( 0 , 0 )??
asked 2022-07-15
This question was asked in CSIR. please help me to find out correct choice

Let y ( t ) satisfy the differential equation
y = λ y ; y ( 0 ) = 1
. Then the backward Euler method for n > 1 and h > 0
y n y n 1 h = λ y n ; y ( 0 ) = 1
yields
1. a first order approximation to e λ n h
2. a polynomial approximation to e λ n h
3. a rational function approximation to e λ n h
4. a Chebyshev polynomial approximation to e λ n h
asked 2022-04-07
For: F ( 0 ) = 0 and F ( x ) = f ( x )
Euler's method: F ( 0 + h ) = F ( 0 ) + h F ( 0 ) = 0 + h f ( 0 )
Continuing the process, F ( 10 h ) = h f ( 0 ) + h f ( h ) + h f ( 2 h ) + . . . . . h f ( 9 h )
This resembles the Riemann sum: Σ i = 1 n f ( x i ) ( x i x i 1 )
Therefore my professor used Euler's method to solve integral problems.

Example: 3 3.09 f ( x ) d x = 0.81. Approximate f ( 3 ) . F ( x ) = h f ( x )
0.81 = 0.09 f ( x )
f ( x ) = 3
My question: How did F ( x + h ) = F ( x ) + h f ( x ) become F ( x ) = h f ( x ) ?
asked 2022-08-12
The problem I have is the initial value problem
y = x + y
with
y ( 1 ) = 3 , y ( 1 ) = 2 , y ( 1 ) = 1
that should be solved with Eulers method using the step length, h = 1 2 .

The iteration step for Eulers method is y n + 1 = y n + h f ( x n , y n ). So I should need a system of equations of my initial values I have. I started with substituting:
U 1 = y , U 2 = y , U 3 = y
and then
U 1 = U 2 , U 2 = U 3 , U 3 = x + U 1
And it's here I'm stuck, I don't understand how I should start iterate with the step-length from here, I have only encounteblack first-order problem with Eulers method so I would love if someone could point me in the right direction.
asked 2022-06-20
Use Euler's method with step size 0.2 to estimate y(0.6) where y(x) is the solution of the initial value problem y' = cos(x+y), y(0) = 0
So on a high level, we're using Euler's method to approximate a function that we don't know but only know the derivative equation for and the initial. We're going to use Euler's to get approximate values of the unknown function using approximations.
So is this right:
original x = 0, y = 0
y 1 = 0 + 0.2 ( c o s ( 0 ) ) = 0.2
so new x = 0.2 and new y = 0.2
y 2 = 0.2 + 0.2 ( c o s ( 0.2 + 0.2 ) ) 0.384
y 3 = 0.384 + 0.2 ( c o s ( 0.4 + 0.384 ) ) = 0.384 + 0.141 0.525
Is that right? The numbers are just going to be hard to work with right?

New questions